Analysis Of Raw Material Inventory Control Of Fresh Fruit Bunches (FFB) Of Palm Oil Using The Continuous Review System Method - Siregar, Almi Rahmadani; Nawawi, Zuhrinal M.; Syarbaini, Ahmad Muhaisin B. (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The purpose of this research is to analyze the management of Fresh Fruit Bunch (FFB) raw material reserves at PT. Austindo Nusantara Jaya Agri (ANJ) Binanga. This is done to alleviate concerns about the decline in Crude Palm Oil (CPO) production and the rising costs of raw materials caused by less than ideal sales. The system used in this analysis is the Continuous Review System. Continuous Review is a technique employed that applies a quantitative and descriptive approach through observation and interviews. The research findings indicate that inventory costs amount to Rp. 315,092,755, which means that the total inventory costs can be reduced, even though previous inventory costs were recorded at Rp. 290,453,600, which appears to be lower. However, due to the minimal stock shortages and the management of waiting times thanks to the contracts agreed upon with suppliers, the effectiveness of the Continuous Review System in that analysis has been proven. This research highlights the urgency for smooth production, which requires the provision of stock and the quality of the final product, as well as offering practical guidelines to maximize inventory management in the palm oil industry.